Functioning features of the labor market in St. Petersburg - N. N. Musinova (Вестник университета)
The rapid changes (global, technological, economic) currently taking place in all spheres of life and creating uncertainty affect the dynamics of the number of marriages, divorces, birth rates, mortality, etc. Such changes transform the established types of employment and labor relations, generally affecting the labor market. In this regard, the basis for the existence of the labor market in the modern economy is a constant shortage of qualified labor supply. It is the shortage of workers of a certain quality and professionalism that causes the presence of unemployment in society. In addition, the domestic labor market has been affected by the coronavirus pandemic and Western sanctions in recent years. The article is devoted to the study of the most important aspects of the functioning of the modern labor market in St. Petersburg, the main problems of its development are diagnosed and the ways to solve them are determined.